The story of my life - Keller, Helen, 1880-1968. (Garden City, N.Y., Doubleday, 1954)
Contains Miss Keller's original biography plus her letters from 1887 to 1901,and an account of her education
Keywords: Keller, Helen, -- 1880-1968.; Sullivan, Annie, -- 1866-1936.; Blind-deaf -- Biography